Determinants of Acute and Late Pulmonary Vein Reconnection in Contact Force–Guided Pulmonary Vein Isolation: Identifying the Weakest Link in the Ablation Chain. (April 2017) - El Haddad, Milad; Taghji, Philippe; Phlips, Thomas; Wolf, Michael; Demolder, Anthony; Choudhury, Rajin; Knecht, Sébastien; Vandekerckhove, Yves; Tavernier, Rene; Nakagawa, Hiroshi; Duytschaever, Mattias
Abstract : Background—: Pulmonary vein reconnection (PVR) still determines recurrences of atrial fibrillation after contact force (CF)–guided pulmonary vein isolation. We studied whether acute PVR (adenosine and waiting time) and late PVR (at repeat) are explained by incomplete transmurality and contiguity within the deployed radiofrequency circle. Methods and Results—: We analyzed 42 CF-guided ipsilateral pulmonary vein isolation procedures. For each radiofrequency tag within the circle, we collected data reflecting lesion depth (time of application, power, impedance drop [Δ-Imp], CF, force–time integral [FTI], and ablation index [AI]) and contiguity (automated interlesion distance [ILD]). Ablation line contiguity index (ALCI) was developed as a novel automated algorithm combining depth and contiguity into one single criterion. Each circle was subdivided into 10 segments. For each segment, we determined its weakest link by annotating timemin, powermin, Δ-Impmin, CFmin, FTImin, AImin, ILDmax, and ALCImin . Compared with segments without PVR (n=758), PVR segments (n=44) were characterized by lower Δ-Impmin (4.8 versus 7.4 Ω), CFmin (8.5 versus 11.8 g), FTImin (351 versus 473 gs), AImin (367 versus 408 arbitrary unit [au]), and higher ILDmax (6.8 versus 5.5 mm). ALCImin was significantly lower in segments with PVR (74% versus 104%; P <0.001) and was associated with the highest accuracy to predict durable segments (area under the curve=0.73). Conclusions—: In CF-guided pulmonary vein isolation, PVR is explained by lack of both lesion depth and contiguity within the deployed radiofrequency circle. ALCI, a novel measure combining contiguity and depth, is the most accurate predictor for durable segments. By avoiding weak links in the ablation chain, ALCI-guided ablation is expected to improve success rate of point-by-point radiofrequency ablation.